Comparasion Of The Therapeutic Effect Between SWD And Tens On Relieving Pain In Mechanical Low Back Pain Petients - Robby Kartadinata; Lanny Indriastuti (RSUP Dr. Kariadi, 2012)
Background : Low back pain (LBP) is the second cause of pain after headache and remains one of the most common symptoms for seeing a physician. About 90% of LBP is caused by mechanical factor. There are various physical modalities to relieve pain, such as, Short Wave Diathermy (SWD) and Transcutaneus Electrical Nerve Stimulation (TENS) which are proved to be useful to relieve pain. The aim of the study is to compare SWD and TENS on relieving pain in mechanical LBP patients. Methods : A pre-posttest study in 36 outpatients, with subacute mechanical LBP, ranging from 30–55 years old, were randomly divided into two even groups, the SWD group and TENS group. The subjects received either SWD or TENS on lumbosacral area for 15 minutes, 3 times a week, with the interval of 2–3 days during 2 weeks. Visual Analogue Scale (VAS) was applied for pain assessments to all subjects before and 24 hours after the sixth therapy session. Results : There was a reduction on VAS score in the SWD group from 4.56 ± 0.62 cm to 1.90 ± 0.51 cm (p<0.001). There was a reduction on VAS score in the TENS group from 4.64 ± 0.59 cm to 2.03 ± 0.50 cm (p<0.001). There was no significant difference on VAS score reduction between SWD and TENS group (p = 0.643). Conclusion : TENS therapy relieves pain in subacute mechanical LBP patients as good as SWD Therapy. Keywords : Mechanical low back pain, SWD, TENS.